The cutaneous intrinsic visceral afferent nervous system: A new model for acupuncture analgesia - Silberstein, Morry (Academic Press, 2009)
The mechanism of acupuncture, whilst not known with certainty, has previously been considered to be stimulatory. A novel hypothesis is presented here in which C fiber tactile afferent axons bifurcate at acupuncture points and then diverge, running along acupuncture meridians, to subsequently communicate with Merkel cells. It is proposed that acupuncture disrupts the bifurcation of these axons, preventing neural transmission between Merkel cells as well as central communication with the spinal cord. Making use of the known phenomenon that acupuncture points have lower electrical resistance than adjacent skin, this hypothesis was tested using an electrical circuit model and successfully predicted the observed 103 reduction in skin resistance at acupuncture points. In addition to explaining acupuncture and the roles of both Merkel cells and C fiber tactile afferents, the model has greater implications for neuroscience, through the postulation of a new division of the autonomic nervous system. © 2009 Elsevier Ltd. All rights reserved.